(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2004)
In this paper, we propose a new approach to solve the problem of the spectral occupation for the transmissions with high flow in satellites telecommunications systems, this occupation spectral is caused by the cohabitation with other emissions or services sharing the same band frequency, this approach is the association of discrete wavelet with convolutional code. The performance of this method are illustrated in a additive white Gaussian noise channel (AWGN).